MENINGKATKAN HASIL BELAJAR SISWA DENGAN METODE REWARD DAN PUNISHMENT DALAM MATA PELAJARAN IPA PADA SISWAKELAS VI SD NEGERI 167644 TEBING TINGGI - Merti Lamria Harianja (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2016)
This purposes of this research is to improve learning result on science subject  through reward and punishment method. This classroom action researchconducted by 2 cycles of the four phases: planning, implementation, observation, reflection. The subjects were students from class VI, SDN 167644 Tebing Tinggi which amounted to 30 students. This study used a qualitative descriptive analysis technique. The results showed that the use of the reward and punishment method of science subjects can improve student learning result characterized by increased mastery learning students, namely the first cycle (80%), cycle II (90%) and complete learn the clasical equal to 90 %. Key Word: reward, punishment, science